Molecular parameters for the gas phase molecules SbO and SbP - Ramachandran Sri P.; Raja V.; Rajamanickam N. (Journal of the Serbian Chemical Society, 2008)
Franck-Condon factors and r-centroids, which are very closely related to relative vibrational transition probabilities, were evaluated by the numerical integration procedure for the bands of the A2Π3/2 - X2Π3/2, C2Σ - X2Π3/2 and D2Π - X2Π systems of the isotopic SbO molecule and for the B1Π - X1Σ+ system of the isotopic SbP molecule, using a suitable potential.